RP-HPLC-based phytochemical analysis and diverse pharmacological evaluation of Quercus floribunda Lindl. ex A. Camus nuts extracts. Issue 13 (15th June 2021) - Ahmed, Madiha; Adil, Muhammad; Haq, Ihsan-ul-; Tipu, Muhammad Khalid; Qasim, Muhammad; Gul, Bilquees
Abstract: Quercus floribunda Lindl. ex A. Camus nuts have important folklore uses, assessed for underexplored biological potential. Nuts galls or cores and coats were utilized for the preparation of extracts using 14 solvent systems. Antioxidant, antimicrobial, cytotoxic and enzyme inhibition assays along with phytochemical profiling was carried out. Distilled water cores extract demonstrated maximum percent yield, phenolics content and total antioxidant capacity. Methanol: ethyl acetate cores extract showed maximum flavonoids content, total reducing power and protein kinase inhibition. Highest percentage radical scavenging and brine shrimp lethality was revealed by acetone: distilled water cores extract. Ethyl acetate cores extract indicated maximum α-amylase inhibition. Methanol: water coats extract showed substantial leishmanial growth inhibition. n -Hexane and chloroform coats extracts showed maximum cytotoxicity against HepG2 and THP-1 cell lines, respectively. Polyphenols quantified through RP-HPLC analysis were quercetin, pyrocatechol, gallic acid, catechin and chlorogenic acid ranging from 0.003 ± 0.001 to 1.785 ± 0.5 μg/mg extract. Abstract : UF0001